Longitudinal studies of exposure to cadmium. Issue 8 (August 1992) - Armstrong, R; Chettle, D R; Scott, M C; Blindt, M; Mason, H J
Abstract : Measurements of urinary proteins, blood and urinary cadmium, and in vivo kidney and liver cadmium have been made for a group of workers at several times between 1981 and 1990. The possibility of the introduction of measurement artifacts due to the use of different in vivo measurement systems has been assessed and is considered to be small. Changes in cadmium body burden with time have been studied in relation to kidney function. The results suggest several interesting patterns, although more data are needed to elucidate these further. They do, however, show the effectiveness of good hygiene in the workplace.